2008
DOI: 10.1186/1471-2121-9-38
|View full text |Cite
|
Sign up to set email alerts
|

The lateral mobility of cell adhesion molecules is highly restricted at septate junctions in Drosophila

Abstract: Background: A complex of three cell adhesion molecules (CAMs) Neurexin IV(Nrx IV), Contactin (Cont) and Neuroglian (Nrg) is implicated in the formation of septate junctions between epithelial cells in Drosophila. These CAMs are interdependent for their localization at septate junctions and e.g. null mutation of nrx IV or cont induces the mislocalization of Nrg to the basolateral membrane. These mutations also result in ultrastructural alteration of the strands of septate junctions and breakdown of the paracell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 34 publications
0
30
0
Order By: Relevance
“…Even 30 minutes post photobleaching, all four SJ proteins showed less than 50% recovery and had not reached a recovery plateau (Fig. 1A,B and supplementary material Movies 1-4) (Laval et al, 2008). Because embryos at this stage frequently moved and rolled making longer time-lapse observations impossible, it was difficult to determine the mobile fraction and the half recovery time (t 1/2 ) of SJ components (see Methods and Materials for details of how these parameters were calculated).…”
Section: The Septate Junction Is Composed Of An Extremely Immobile Mumentioning
confidence: 99%
See 2 more Smart Citations
“…Even 30 minutes post photobleaching, all four SJ proteins showed less than 50% recovery and had not reached a recovery plateau (Fig. 1A,B and supplementary material Movies 1-4) (Laval et al, 2008). Because embryos at this stage frequently moved and rolled making longer time-lapse observations impossible, it was difficult to determine the mobile fraction and the half recovery time (t 1/2 ) of SJ components (see Methods and Materials for details of how these parameters were calculated).…”
Section: The Septate Junction Is Composed Of An Extremely Immobile Mumentioning
confidence: 99%
“…S4) (Fehon et al, 1994;Baumgartner et al, 1996;Behr et al, 2003;Genova and Fehon, 2003;Paul et al, 2003;Schulte et al, 2003;Faivre-Sarrailh et al, 2004;Llimargas et al, 2004;Wu et al, 2007;Nelson et al, 2010). In addition, a previous study has shown that mutations in several SJ-associated components affect the FRAP stability of Nrg-GFP and Nrx-IV-GFP (Laval et al, 2008). To further examine the effects of SJ mutations on SJ protein complex formation, we measured the mobility of GFP-tagged ATP, Nrv2, Nrx-IV and Nrg in different SJ mutant backgrounds (Fig.…”
Section: Genetic Analysis Of Components Required For Immobile Sj Compmentioning
confidence: 99%
See 1 more Smart Citation
“…Behr et al, 2003;Genova and Fehon, 2003;Paul et al, 2003;Faivre-Sarrailh et al, 2004;Tiklová et al, 2010). Fluorescence recovery after photobleaching (FRAP) experiments have revealed that SJ proteins are essentially fixed in the membrane by stage 14 of embryogenesis (Laval et al, 2008;Oshima and Fehon, 2011). Mutations in any core SJ gene increases the mobility of other SJ proteins at stage 14, further demonstrating the highly stable and interdependent nature of the SJ complex.…”
mentioning
confidence: 99%
“…Third, the Cad99C-and SASmislocalized domains are mutually exclusive with the remaining lateral domains, where SJ proteins localize. The elongated SJ protein distribution could be due to the SJ structures being disrupted because a dye exclusion assay revealed compromised barrier function in the completely rounded Cad99C-or SAS-overexpressing SG cells (data not shown) and because mislocalization of SJ proteins into the entire basolateral domain has been reported in many SJ mutants (Laval et al, 2008;Nelson et al, 2010;Paul et al, 2003;Wu et al, 2004). Alternatively, the elongated SJs could be due to cells establishing new SJ domains in more basolateral regions in response to the new apical domains being established nearby.…”
Section: Discussionmentioning
confidence: 94%